Air Pollution, Health Expenditures, and Respiratory Mortality: An Efficiency Analysis of OECD Countries - Zeliha Çelik; Fulden Sari; Fevzi Akbulut (Bingöl Üniversitesi Sağlık Dergisi, 2026)
Air pollution and environmental problems cause respiratory morbidity and mortality worldwide. This study aimed to evaluate the impact of particulate matter (PM2.5), greenhouse gas emissions, and health expenditures on mortality from respiratory diseases in selected OECD countries. This cross-sectional study included 17 OECD countries with complete data for 2023. An input-oriented Data Envelopment Analysis (DEA) model was used to assess the efficiency of the countries. PM2.5 emissions, greenhouse gas emissions (CO₂-equivalent), and per capita health expenditure were used as input variables, while mortality from respiratory diseases (per 100,000 inhabitants) was defined as the output variable. The mean efficiency score was 0.733, and six countries were identified as efficient. Tobit regression results indicated that PM2.5 emissions were significantly and negatively associated with super-efficiency scores (β= -0.133, p< 0.05). Health expenditure per capita also showed a negative significant association (β= -0.000114, p= 0.05), while greenhouse gas emissions were not significantly related to super-efficiency scores (p> 0.05). Health expenditures alone may not increase efficiency without effective environmental control strategies. These findings emphasize importance of integrating environmental policies into health system planning to reduce the burden of respiratory diseases.